How do local government information sources affect the purchase willingness of low-carbon agricultural products? The example of regional brand agricultural products - Xu, Pu; Wang, Linlin; Li, Yufeng; Liu, Min (Frontiers in Public Health, 2023)
Introduction: In order to achieve the carbon peaking and carbon neutrality goals, the agricultural sector has been given high priority to reduce carbon emissions. Since consumption is the ultimate goal of production, the consumption of low-carbon agricultural products is of great significance to promote the reduction of agricultural carbon emissions. Regional brand agricultural product is an important tool to promote the development of regional economy to "green, low-carbon, branded and high-quality", and has the technical and institutional conditions to develop into low-carbon agricultural product, so this study takes regional brand agricultural products as the representative of low-carbon agricultural products. As a information source to guide the public to consume in the green and low-carbon way, local government can effectively develop the market for low-carbon agricultural products and drive the development of low-carbon agriculture from the demand side. Methods: Based on structural equation model with bootstrap method, this paper focuses on the mechanism of the influence of local government information source characteristics (credibility, professionalism, and attractiveness) on consumers' willingness to purchase low-carbon agricultural products, and explores the mediating role of perceived benefits and perceived risks. Results: The following findings are established: first, the credibility and professionalism of local governments play a positive role in influencing the purchase willingness of low-carbon agricultural products through perceived benefits, with credibility having the greatest degree of influence. Second, the attractiveness of local governments positively influences consumers' willingness to purchase low-carbon agricultural products through perceived risk. Third, perceived benefits play a fully mediating role between credibility and purchase intention, play a partially mediating role between professionalism and purchase willingness, perceived risks play a partially mediating role between attractiveness and purchase willingness. Discussion: This study provides new ideas for the construction of low-carbon agricultural products and low-carbon development in the agricultural sector from the perspective of local government information sources.